Habitar um mundo de imagens: reflexões sobre os sentidos e sobre a imaginação por meio das fotografias de Evgen Bavcar - Baroni, Rodrigo Frare [UNIFESP] (2019)
This research aims to explore and problematize the political and multisensorial dimensions of the photographic image through the case study of the photographs and texts of blind photographer and philosopher Evgen Bavcar. Based on the considerations made by Bruno Latour (2008) and Jaques Rancière (2017), I propose to think of photography as a machine of affections (that is, as a way of producing and engendering differences in the world that produces both a sensory environment and a sensitive medium based on collective assemblages that involve both human and non-human actors, in a process that produces simultaneously: bodies, desires, affections and policies) able to transit between different regimes of visibility.